THE INFLUENCE OF STRATEGIC TRAINING ON EMPLOYEE PERFORMANCE IN THE PUBLIC SECTOR IN KENYA: A CASE STUDY OF THE KENYA COPYRIGHT BOARD - Arucy, Ketty Ghatete; Juma, Dr. Dennis (European Journal of Business and Strategic Management, 2018)
Purpose: The motive of this study was to establish the Influence of Strategic Training on Employee Performance in the Public Sector in Kenya; the case of KECOBO. Methodology: This study employed a descriptive survey design. The population of the study were all (42) officers currently serving at the Kenya copyright Board; a Public Service agency responsible for administration and protection of copyright and related rights in Kenya. The study did not use a sample. The respondents who responded to the questionnaire were 36 who included a combination of managers and non-managers. For the analysis to be effective, the entire population was used. Primary data was collected using questionnaires which were pretested for reliability and validity to determine it suitability for use in the study. Cross tabulation and Analysis of Variance was employed to test for significance in differences on various responses. Analysis of the Quantitative data collected was done using SPSS (Version 22). Quantitative data was analysed using descriptive and inferential statistics and results presented using charts and tables. Results: The study shows that strategic training has a positive influence on the ability of the employee to perform given tasks. It has shown that staff trainings at KECOBO is not fully dependent on the employee needs but on the organisation needs. Through need based, competence and demand driven training, employees are equipped with the necessary skills to take on important tasks and they work efficiently and are personally responsible for their job outcomes. The study also reveals that after receiving training based on the employee and organisation needs, there is improved work commitment, productivity and teamwork. Unique Contribution to Theory, Policy and Practice: The study recommended that the various schemes of service for different cadres of staff in the public sector should be reviewed to conform to the current job demands and, periodic training impact assessment undertaken across the public sector to confirm the reliability and sustainability of established training programmes.